Lembaga Tabung Haji (TH): relationship between encouragement rewards scheme for Malaysia's school with customer behavior / Mohd Faizal Mohamad - Mohamad, Mohd Faizal (Faculty of Business and Management, 2007)
Lembaga Tabung Haji (TH) operates as an alternative financial institution providing "halal" investment opportunities to Malaysian Muslim depositors. Facing new competition from other financial institutions, which providing Islamic bank service, TH management feels that TH must provide the highest quality service with innovative products that are profitably delivered and exceed the customers' expectations. The objectives of the study are to identify how effective the Encouragement Rewards Scheme for Malaysia's School (ERSMS) in creating desire and actual action among its potential customers and also to identify which marketing tools that can be used by TH effectively in attracting new customers. In this context, the ERSMS effectiveness is focus to four stages which are Attention, Interest, Desire, and Action. The cluster sampling (probability sampling technique) is used for the study. which the target population is first divided into mutually exclusive and collectively exhaustive subpopulations. Then a random sample of clusters is selected. This study is based on two categories, namely primary schools and secondary schools. Based on the study, the most important stage that ranked by the TH's respondents is Desire Stage. Based on the findings, some suggestions have been recommended to TH to come up with new strategies to enhance the company promotion tools in attracting new customers.